Risk of cardio-respiratory abnormalities in preterm infants placed in car seats: a cross-sectional study - Hegyi Thomas; Mehta Rajeev; Petrova Anna; Ojadi Vallier C (BMC, 2005)
Abstract Background Little is known about the factors that predispose to the occurrence and severity of cardio-respiratory symptoms during the placement of a prematurely born infant in a car seat. The impact of gestational age, weight at discharge and infant's pre-existing cardio-respiratory status (in the supine position) on cardio-respiratory function during pre-discharge testing in a car seat (semi-upright position) has not been investigated. Methods The cardio-respiratory function of 42 preterm neonates with gestational age 24 to 35 weeks and discharge weight 1790 to 2570 grams were monitored for 45 minutes before, during, and after placement in a car seat. The occurrence of periodic breathing, apnea, bradycardia, or decreased oxygen saturation (SaO2) was analyzed. Results Prior to the car seat testing, 15 (35.7%) infants displayed one or more abnormalities of cardio-respiratory function. During the car seat testing, 25 (59.6%) infants had periodic breathing, 33 (78.2%) had oxygen saturation <90%, 14 (33.3%) had bradycardia less than 80 beats per minute, and 35 (83.3%) had a combination of these symptoms. Infants, both with and without pre-existing cardio-respiratory abnormalities, had an almost equal probability (80% vs. 83.3%) for the development of cardio-respiratory symptoms during placement in the car seat. Weight at discharge ([less than or equal to] 2,000 grams) but not the gestational age (<28 weeks or [greater than or equal to] 28<37 weeks), was associated with either increased episodes of oxygen desaturation or the combination of cardio-respiratory symptoms that were seen during the placement of these infants in the car seat. Repositioning from the car seat to the supine position showed normalization of cardio-respiratory function in the majority (83%) of the tested infants. None of the tested clinical factors were associated with the severity of the cardio-respiratory symptoms. Conclusion Pre-discharge testing of the cardio-respiratory function of preterm infants during placement in a car seat is important for the prevention of cardio-respiratory symptoms during their transportation. However, the high risk for developing cardio-respiratory symptoms will require the consideration of an alternative mode of safe home transportation for preterm infants; especially those with a discharge weight less than 2,000 grams.